Hybrid Oven (Solar + Biomass) for Cooking. Design, Construction and Thermal Evaluation - Quiroga, Viviana Noelia (2019)
Solar energy for cooking is an interesting option to achieve energy efficient cooking, while reducing environmental impact and facilitating nutritious cooking on a daily basis, especially to provide nutrition for young children. Solar oven delivers high thermal performance running on solar energy alone on clear days. On cloudy days, the amount of solar energy is not enough to use the solar oven. Therefore, it is necessary to cook with electricity, gas or firewood, which breaks the continuity of the use of the solar oven. Then, when it is possible to use the solar oven again (on the subsequent clear day), it is difficult because of the habit established of fuel use. The hybrid oven (solar + biomass) allows for cooking every day of the year (clear or cloudy), with the same device, even at night. This paper presents the design, construction and thermal evaluation of a hybrid solar oven with biomass as an auxiliary source of energy. The basis is the drum solar oven, widely used for its characteristics: easy to build, efficient performance and optimum cooking capacity. It incorporates a specially designed appliance which takes advantage of the biomass and generates energy efficient cooking. Thermal tests are carried out to determine the characteristic parameters: figures of Merit F1 =0.100; F2 =0.253, standardized cooking power for 50°C, 31.2 W, and cooking efficiency 23.3% for operation only with solar energy and standardized cooking power for 50°C, 378.3W and cooking efficiency 5.8% for the oven with hybrid operation. Temperatures reached by the absorber plate are 120°C for solar-only energy operation and 173°C for hybrid operation. These temperatures do not endanger the integrity of the materials used. Only a minimum amount of energy is needed to reach the necessary temperature and power for cooking. It is therefore an interesting and economical solution for all communities of any climatic condition, especially those that are isolated from energy supply networks.